Respostas
respondido por:
77
An = A1 + ( n - 1 ) . r
86 = A1 + ( 23 - 1 ) . 4
86 = A1 + 22 . 4
86 = A1 + 88
A1 = 86 - 88
A1 = -2
86 = A1 + ( 23 - 1 ) . 4
86 = A1 + 22 . 4
86 = A1 + 88
A1 = 86 - 88
A1 = -2
dannysantos123:
Obrigada ''
respondido por:
25
Utilizando a fórmula do termo geral de uma progressão aritmética (PA):
Onde:
= enésimo termo
= primeiro termo
n = número de termos
r = razão
Bons estudos!!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás